Does Large‐Scale Crustal Flow Shape the Eastern Margin of the Tibetan Plateau? Insights From Episodic Magmatism of Gongga‐Zheduo Granitic Massif - Fangyang Hu; Fu‐Yuan Wu; Mihai N. Ducea; James B. Chapman; Lei Yang (Geophysical Research Letters)
Abstract The mechanisms driving crustal deformation and uplift of orogenic plateaus are fundamental to continental tectonics. Large‐scale crustal flow has been hypothesized to occur in eastern Tibet, but it remains controversial due to a lack of geologic evidence. Geochemical and isotopic data from Cenozoic igneous rocks in the eastern Tibet‐Gongga‐Zheduo intrusive massif, provide a way to test this model. Modeling results suggest that Cenozoic magmas originated at depths of ∼30–40 km, the depth that crustal flow has been postulated to occur at. Detailed isotopic analyses indicate that the igneous rocks are derived from partial melting of the local Songpan‐Ganzi crust, arguing against a long‐distance crustal flow. Episodic magmatism during the Cenozoic showing a repeated shifting of magmatic sources can be correlated with crustal uplift. The continued indentation of the Indian Block and upwelling of the asthenosphere contribute to the crustal deformation, magmatism, and uplift.